Vocal instability over time in individual male European nightjars, Caprimulgus europaeus: recommendations for acoustic monitoring and surveys. Issue 3 (3rd May 2020) - Raymond, Sarah; Spotswood, Sarah; Clarke, Hazel; Zielonka, Natalia; Lowe, Andrew; Durrant, Kate L.
ABSTRACT: Acoustic monitoring of birds is developing rapidly as equipment, methods and analyses improve. However, most population monitoring studies still utilise traditional techniques like mark-recapture or line transects. Previous researchers used vocal recordings of male European nightjars, Caprimulgus europaeus, to identify individuals, finding that four acoustic parameters correctly assigned 98.5% of calls to individuals. We tested their methods on a population of European nightjars recorded over two successive breeding seasons and found that percentage of males correctly classified within a season reached a maximum of 73.5%, rising to 75% if full-length calls and 13 acoustic parameters were used. We tested whether males could be re-identified over a two-year period and found that only 20% of calls were assigned to the same putative territorial individuals, despite separate ringing data showing that males can maintain site fidelity for up to eight years. Our results indicate that the characteristics of male nightjar vocalisations may alter over time. We therefore recommend that vocal discrimination be used in conjunction with existing monitoring techniques when surveying for population monitoring, that as many call parameters as possible are used and that recording for automated presence/absence surveys takes place over a short time-frame.